Teach yourself CGI programming with Perl 5 in a week - Herrmann, Eric.; Herrmann, Eric. (Indianapolis, Ind. Sams.net, 1997)
CD-ROM includes the source code for the book's programs, plus pre-packaged libraries of CGI programs.
Includes index.
Rev. ed. of: Teach yourself CGI programming with Perl in a week / Eric Herrmann. 1st ed. 1996.
System requirements: Windows (all versions), DOS, or UNIX.
Keywords: Web servers -- Computer programs; CGI (Computer network protocol).; Perl (Computer program language).